Development of Traditional Sport Game Model “Bentengan” for Student’s Physical Fitness in Sports and Health Physical Education Learning (Case Study on Class IV MI Students of Maduran Lamongan District) - Moh. Syobil Birri; Agus Hariyanto; Abdul Rachman Syam Tuasikal (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
The purpose of this development research is to improve physical fitness in the Physical Education learning process. The development of the traditional sports game model "Bentengan" is carried out in several stages: needs analysis, product manufacturing, evaluation and validation, phase I trials, product revisions, phase II trials, stage 2 product revisions (last revision). The subjects of this study were fourth grade students of MI from Madrasah Ibtidaiyah in Maduran sub-district, Lamongan Regency (MIM 10 Gedangan, MIM 1 Pangkatrejo, MI NU Pangkatrejo, and MI Al-Islamiyah Parengan). Expert validation was carried out by two experts. The first phase of the experiment was carried out on 25 students with 1 PJOK teacher and the second stage test was carried out by 71 students with 3 PJOK teachers. The process of collecting data using a questionnaire. This data consists of evaluations for product quality, suggestions for product improvement, and student responses to game models. The result of this research is the product development model of the game "Bentengan" which is packaged in the form of a book to support learning activities and instructions for implementing the game. Based on data from trial results (small group) and field trials (large group), there were no revisions made by researchers on products that had been developed because the percentage of product development reached 89.53% cognitive aspects with very good categories, 90.39% affective aspects with very good category, and 88.13% psychomotor aspects with very good category, so it is feasible to use. Based on the data analysis, it can be concluded that the result of this research is that the product development model of the game "Bentengan" in Penjasorkes learning can be used to improve physical fitness for grade IV Madrasah Ibtidahiyah in Maduran District, Lamongan Regency.